Peran Kebijakan Fiskal dan Moneter Islam dalam Mewujudkan Keadilan - Nurul Istiqomah; Maghfira Izzany; Aliya Nurhasanah (Journal of Islamic Economics and Finance, 2025)
The continuing economic inequality in Indonesia reflects the need for alternative approaches in macroeconomic policy. This study aims to analyze the integrative role of Islamic fiscal and monetary policies in realizing sustainable economic justice. The method used is a literature study of various relevant national and international scientific journals. The results show that Islamic fiscal policy through zakat and waqf instruments plays a role in wealth redistribution, while usury-free and real sector-oriented Islamic monetary policy maintains economic stability in an ethical manner. Compared to conventional economic systems, the Islamic approach offers a balance between spiritual values and economic effectiveness. The findings also show the importance of institutional synergy, public literacy, and integrated regulation to optimize the integration of the two policies. The implications of this research provide theoretical contributions for the development of Islamic economic models and offer strategic recommendations for the formulation of more equitable and inclusive public policies.